Religion, Media and Piety Construction: A Study of the Web Series Entitled Ustad Millenial - Aula, Annidaul (DINIKA : Academic Journal of Islamic Studies, 2022)
This article aims to expand the discussion of the identity of piety in the web series with the Islamic genre, Ustad Milenial, which airs on WeTV and Iflix. Identity is a crucial problem in social life. In the web series, the pious identity of a muslim is different from the identity of piety shown in previous Islamic popular cinema, both in terms of story plots, characters, and symbols used in building a pious identity. The focus of the discussion in this article is how the identity of piety is built in this web series, and why is the identity of piety in this web series described in such a way? Based on a qualitative approach with a constructivist paradigm, and discourse analysis, I argue that there is an alternative to the identity of piety depicted in the Ustad Milenial web series. The results of this study indicate that the identity of piety in the Ustad Milenial web series is constructed through the appearance of youth muslims who are more trendy and hits, the noble ideals of a muslim in maintaining Islam, a strict religious education background for an authority, devotion and affection for parents, religious knowledge of youth muslim, the use of digital technology as a medium of da'wah, love stories that are identical with young people, and the inter-religious tolerance.